ANALYZING FINANCIAL PERFORMANCE IN PT. BANK MANDIRI (PERSERO) TBK - Kamal, Sri Wahyuni Anggraini (Sam Ratulangi University, 2015)
ABSTRACT With the influence of the current global economic developments, which could lead to economic competition is very tight so it requires other factors that support the strengthening of the economic structure so that the economy of a country must be strong in the face of global economic competition. The Purpose of this research is to analyze whether there is significant difference on financial performance of PT. Bank Mandiri (Persero) Tbk of the last 5 years (2010-2014). The sampling technique used is a purposive sampling.This research is comparative study, because the purpose is to analyze and compare the data of the last 5 years. The objects of this research are provided in Bank Mandiri annual reports. This Current Research using a judgment sampling method. From the result, that the Financial Performance in PT. Bank Mandiri (Persero) Tbk at the last 5 years there was increase from year to year. Keywords : Financial, Fundamental Factor, Current Ratio, ROA, ROE, NIM, CAR, LDR, EPS